OPTIMASI SISTEM PENCAHAYAAN DENGAN MEMANFAATKAN CAHAYA ALAMI (STUDI KASUS LAB. ELEKTRONIKA DAN MIKROPROSESSOR UNTAD) - Nurhani Amin (Foristek, 2011)
A good lighting system has to meet three criteria; quality and quantity of light and efficient powerconsumption. A good lighting room will help effective activities inside the laboratorium. To achieve an optimum lighting, natural light has to be considered in the installation design. To optimise lighting installation of the building Elecronics and Microprosessor Laboratorium, clusteringluminer with the switch has to proportionately adjust according tothe sun light incidence to the laboratorium.